Pulsed Lasers for Industrial Applications: Fiber, slab and thin‐disk: Ultrafast laser technology for every application. Issue 2 (17th April 2018) - Jansen, Florian; Budnicki, Aleksander; Sutter, Dirk
Abstract: Material processing with ultrashort pulses provides the user with a variety of benefits. The significantly reduced heat affected zone and the ability to machine numerous different materials are the most striking features. The key for commercial viability of industrial ultrashort‐pulse lasers is long‐term reliability in an industrial environment in combination with sufficient parameter flexibility in terms of different pulse lengths, pulse energies, and pulse repetition rates. Trumpf's TruMicro laser portfolio is designed to fulfill these requirements by using the know‐how of many tens of thousands of operational hours for individual lasers and accumulated tens of millions of operational hours in industrial environment. The TruMicro portfolio includes nanosecond lasers of up to 2000 W average power within the TruMicro 7000 series. The ultrashort‐pulse lasers TruMicro 2000 and TruMicro 5000 currently cover a power range of 10 – 150 W and are based on fiber‐ and, respectively, thin‐disk technology.